The Effects of Gadget Exposure on Social Interaction Skills among Preschool Children (Ages 3–5) at KOBER and TK Miftahul Jannah - Aziezah, Luthfia; Karyamah, Imas; Sahlani, Lalan (Institut Agama Islam Persis Bandung, 2025)
One form of information technology development that is now closely related to our lives is gadgets. Parental supervision when children use gadgets by giving them rules when they use gadgets. This study aims to gain a better understanding of how gadget use can affect children's social interactions, so that parents and educators can be guided on how to control gadget use more wisely. A quantitative method with data analysis using simple linear regression. The research population consisted of 34 respondents. The research was conducted through field observation by distributing questionnaires to the relevant parties regarding the issues being studied and conducting direct observations of the forms applied when children use gadgets. The problems that emerged in this study were in terms of children's social interaction in the classroom during learning. Some children were unable to interact well with their peers, experienced speech delays, and tantrums due to insufficient supervision by parents when children used gadgets. The research results showed that the T-value was 5.523 and the T-table value was 2.037, with a significance level of 5% and N = 32. Additionally, the variables used in the study have a significant level or probability of 0.00 0.05, indicating that they are significant. Therefore, the t-value is greater than the t-table value, i.e., 5.523 is greater than 2.037, indicating that the use of gadgets has a significant impact on children's social interaction at KOBER and TK Miftahul Jannah